Construction of pH‐sensitive Her2‐binding IgG1‐Fc by directed evolution. Issue 8 (August 2014) - Traxlmayr, Michael W.; Lobner, Elisabeth; Hasenhindl, Christoph; Stadlmayr, Gerhard; Oostenbrink, Chris; Rüker, Florian; Obinger, Christian
Abstract For most therapeutic proteins, a long serum half‐life is desired. Studies have shown that decreased antigen binding at acidic pH can increase serum half‐life. In this study, we aimed to investigate whether pH‐dependent binding sites can be introduced into antigen binding crystallizable fragments of immunoglobulin G1 (Fcab). The C‐terminal structural loops of an Fcab were engineered for reduced binding to the extracellular domain of human epidermal growth factor receptor 2 (Her2‐ECD) at pH 6 compared to pH 7.4. A yeast‐displayed Fcab‐library was alternately selected for binding at pH 7.4 and non‐binding at pH 6.0. Selected Fcab variants showed clear pH‐dependent binding to soluble Her2‐ECD (decrease in affinity at pH 6.0 compared to pH 7.4) when displayed on yeast. Additionally, some solubly expressed variants exhibited pH‐dependent interactions with Her2‐positive cells whereas their conformational and thermal stability was pH‐independent. Interestingly, two of the three Fcabs did not contain a single histidine mutation but all of them contained variations next to histidines that already occurred in loops of the lead Fcab. The study demonstrates that yeast surface display is a valuable tool for directed evolution of pH‐dependent binding sites in proteins.